2012 Annual Meeting of the Safety Pharmacology Society: spotlight on targeted oncology medicines. (July 2013) - Cavero, Icilio
<x xml:space="preserve">Abstract</x> Introduction: The 12th Annual Meeting of the Safety Pharmacology (SP) Society (SPS) covered various subjects among which safety issues concerning oncolytic drugs are reviewed and discussed in details. Areas covered: The challenges faced by a medical oncologist during the development of new anticancer medicines were the focus of the keynote address. Romidepsin, a drug initially abandoned because of serious cardiotoxicity in dogs, was successfully rescued for clinical evaluation by tailoring the dose regimen to mitigate cardiac toxicity risks. The integration of SP endpoints into long-term toxicology offers the advantage of determining safety on organ function during chronic exposures, whilst also supporting the principal goals of the 3Rs framework. State-of-the-art imaging technologies can provide valuable, interpretable and translational (human to mouse to human) data for the detection of myocardial function impairment. The future growth of SP was discussed in terms of areas in need of innovative approaches as identified, in particular, in a worldwide sharing of SP data and methodologies. Expert opinion: The need for epochal changes to ensure a bright future for SP should be promoted by the SPS. These comprise chiefly the expansion of the SP birth charter from primarily a regulatory discipline to include an efficiently organized experimental discovery science for which the name Exploratory SP (ESP) is proposed. Its mission would be the early and cost-effective assessment of the safety of clinical drug candidates on organ function based on mechanistic grounds and conducted outside of current expensive and time-consuming regulatory frontiers and constraints. The implementation of a high standard ESP discipline could also promote the gradual replacement of standalone safety investigations with SP assays performed within long-term toxicity studies.